Passive Ground‐Based Optical Techniques for Monitoring the On‐Orbit ICESat‐2 Altimeter Geolocation and Footprint Diameter. Issue 10 (30th September 2021) - Magruder, Lori; Brunt, Kelly; Neumann, Thomas; Klotz, Bradley; Alonzo, Michael
Abstract: Corner cube retro‐reflectors (CCRs), passive optical components, are used to independently evaluate the geolocation accuracy and effective laser footprint diameter of NASA's laser altimetry mission, ICESat‐2, at two specific study sites: White Sands Missile Range in New Mexico and along a segment of the 88°S line of latitude in Antarctica. The CCR methodology provides ICESat‐2 the ability to monitor these altimeter performance metrics throughout the mission lifetime as an indicator of the health of the instrument and the quality of the observations for science applications. The results using this technique reveal a mean geolocation accuracy of the ICESat‐2 measurements of 3.5 m ± 2.1 m, meeting the mission requirement of 6.5 m. For those instances where multiple CCRs are illuminated, the mean effective laser footprint diameter is 10.9 m ± 1.2 m, with the variability assumed to be due to the influence of atmospheric conditions, but warrants further investigation. Plain Language Summary: NASA launched its second Earth observing laser altimeter in 2018 with mission objectives of studying the changes in our climate by monitoring global elevations, particularly in the polar regions. Since the mission is focused on generating accurate elevations and elevation change assessments, the geolocation accuracy of the measurements is of upmost importance to each of the scientific disciplines supported by these observations. Geolocation validation is required to ensure that the mission is meeting its science objectives. One validation technique uses small optical reflectors that provide a unique signal back to the satellite. These signal locations within the ICESat‐2 data can be compared to the surveyed positions of the optics to determine the data quality. Results from this technique indicate that the measurements are accurate to within 3.5 m, with a standard deviation of 2.1 m. In addition, the optics can be used to determine the effective laser footprint diameter on the surface when multiple optics are illuminated during a single satellite overpass. For those qualifying overpasses, the diameter is estimated to have an average value of 10.9 m with a standard deviation of 1.2 m. The variation in diameter is thought to be a result of environmental influences on the laser‐energy‐level at the surface, most likely linked to atmospheric conditions. Key Points: Corner cube retro‐reflectors are passive optical components that provide a distinct and recognizable reflection signature to space‐based lidar for validation of the measurement geolocation The passive optics also provide a methodology for determining the diameter of the laser footprint on the surface and the effects of the atmospheric attenuation on the effective footprint diameter Validation studies confirm that the accuracy ICESat‐2 geolocation at both mid‐latitude and polar regions currently meet the mission requirement for position quality